2021
DOI: 10.3390/ph14111106
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Hydroalcoholic Extracts from the Ancient Apple Mela Rosa dei Monti Sibillini in Transient Global Ischemia in Rats

Abstract: The Mela Rosa dei Monti Sibillini is an ancient apple variety cultivated by Romans in the foothills of the Sibillini Mountains, central Italy, showing potential as a source of nutraceuticals. The purpose of this study was to evaluate the protective effects of the hydroalcoholic extracts from the peel (APE) and pulp (APP) of this fruit in an animal model of transient global ischemia. Chemical constituents were analyzed by liquid chromatography–mass spectrometry (LC-DAD-MSn) indicating several polyphenols such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Vascular wall lesions and hemodynamic changes are the main factors in the pathogenesis of ischemic stroke ( Thon and Jovin, 2021 ; Zhang et al, 2021 ), which is consistent with our results. On the basis of atherosclerosis, hemodynamic changes, cerebral perfusion, decreased embolus clearance and decreased establishment of collateral circulation in the ischemic area, brain cells become hypoxic and apoptotic, forming a central necrotic area and a surrounding ischemic penumbra ( Yousefi-Manesh et al, 2021 ); this process is accompanied by excessive release of free radicals, intracellular calcium overload, and excitatory amino acid toxicity, resulting in neuronal damage ( Catanese et al, 2017 ; Uzdensky, 2019 ). Therefore, neuroprotective therapy is particularly important in the treatment of AIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular wall lesions and hemodynamic changes are the main factors in the pathogenesis of ischemic stroke ( Thon and Jovin, 2021 ; Zhang et al, 2021 ), which is consistent with our results. On the basis of atherosclerosis, hemodynamic changes, cerebral perfusion, decreased embolus clearance and decreased establishment of collateral circulation in the ischemic area, brain cells become hypoxic and apoptotic, forming a central necrotic area and a surrounding ischemic penumbra ( Yousefi-Manesh et al, 2021 ); this process is accompanied by excessive release of free radicals, intracellular calcium overload, and excitatory amino acid toxicity, resulting in neuronal damage ( Catanese et al, 2017 ; Uzdensky, 2019 ). Therefore, neuroprotective therapy is particularly important in the treatment of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Another independent group of MCAO and LRP mice was scored on the modified Neurological Severity Scale (mNSS) ( Yousefi-Manesh et al, 2021 ). The mNSS was applied to determine neurological function by a researcher blinded to the experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained in the experiment correspond with the literature data that the polyphenolic compounds contained in the studied concentrate are able to normalize the antioxidant-prooxidant balance, resulting in LPO inhibition. Thus, marked suppression of oxidative stress (decrease in the content of reactive oxygen species and nitrogen and TBA reactants, as well as increased activity and expression of antioxidant enzyme genes) in various tissues with different pathologies is accompanied by prooxidantantioxidant balance (Xiang et al, 2017;Sedlak et al, 2018;Chang et al, 2021;Yousefi-Manesh et al, 2021). The ability of Concentrate to inhibit ascorbate induced LPO may be related to the binding of iron ions by polyphenols, which are required for induction of LPO by ascorbate.…”
Section: Discussionmentioning
confidence: 99%
“…The antiapoptotic (Liu et al, 2021) and antitumour (Martino et al, 2019) activities of apple fruit concentrates have also been demonstrated. In addition, prophylactic administration of apple polyphenols has been shown to reduce pathological changes caused by cerebral ischemia (Yousefi-Manesh et al, 2021), can prevent lung disease development and progression (Birru et al, 2021) and liver fatty infiltration (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Next, sections were dehydrated in ethanol and xylene, then covered with a fluorescent mounting medium. The sections were observed under an Olympus BX50 fluorescence microscope ( 39 ).…”
Section: Methodsmentioning
confidence: 99%